Modeling the Competitiveness of Indonesian Palm Oil Industry: A Conceptual Model Using Hierarchical Multi-Level System Approach - Roland Y.H. Silitonga; Senator Nur Bahagia; Tota Simatupang; Joko Siswanto (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2013)
Indonesian Palm Oil Industry has the largest market share in the world, but still faces problems in order to strengthen the level of competitiveness. Those problems are in the industry chains, government regulation and policy as meso environment, and macro economic condition. Therefore these three elements should be considered when analyzing the improvement of competitiveness. Here, the governmental element is hoped to create a conducive environment. This paper presents the industry competitiveness conceptual model, using hierarchical multilevel system approach. The Hierarchical multilevel system approach is used to accommodate the complexity of the industrial relation and the government position as the meso environment. The step to develop the model firstly is to define the relevant system. Secondly, is to formulate the output of the model that is competitiveness in the form of indicator. Then, the relevant system with competitiveness as the output is built into a conceptual model using hierarchical multilevel system. The conceptual model is then discussed to see if it can explain the relevant system, and the potential of it to be developed into mathematical model.